Intracellular Dual Fluorescent Lightup Bioprobes for Image‐Guided Photodynamic Cancer Therapy. Issue 28 (20th June 2016) - Han, Haijie; Jin, Qiao; Wang, Haibo; Teng, Wenzhuo; Wu, Jina; Tong, Hongxin; Chen, Tingting; Ji, Jian
Abstract : An intracellular dual fluorescent light‐up bioprobe with aggregation‐induced emission features and endogenously producing photosensitizer protoporphyrin IX (PpIX) abilities is designed and synthesized. The bioprobe is nonemissive in physiological environment. However, the bioprobe can selectively light up cancer cells with blue fluorescence of tetraphenylene (TPE) and red fluorescence of PpIX, owing to the release of TPE and methyl aminolevulinate after targeted internalization by cancer cells. Moreover, upon endogenous generation and accumulation of PpIX in cancer cells, efficient photodynamic ablation of cancer cells after light irradiation is demonstrated with easy regulation for optimal therapeutic efficacy. The design of such dual fluorescent light‐up bioprobes might provide a new opportunity for targeted and image‐guided photodynamic cancer therapy. Abstract : An intracellular dual fluorescent lightup bioprobe is designed and synthesized. It can selectively light up cancer cells with blue fluorescence of tetraphenylene and red fluorescence of protoporphyrin IX (PpIX). Moreover, upon endogenous generation and accumulation of PpIX in cancer cells, efficient photodynamic ablation of cancer cells after light irradiation is demonstrated with easy regulation for optimal therapeutic efficacy.